2001
DOI: 10.1021/jo010540u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Redox Behavior of Azulene-Substituted Benzene Derivatives and (η5-Cyclopentadienyl)[tetra- and di(6-azulenyl)cyclobutadiene]cobalt Complexes

Abstract: 1,2-Di(6-azulenyl)tetraphenylbenzenes and (6-azulenyl)pentaphenylbenzenes were synthesized by Diels-Alder reactions of di(6-azulenyl)acetylenes and 6-(phenylethynyl)azulenes with tetraphenylcyclopentadienone. Cobalt-mediated cyclooligomerization of mono- and di(6-azulenyl)acetylenes afforded 1,3,5- and 1,2,4-tri(6-azulenyl)benzene derivatives together with (eta(5)-cyclopentadienyl)[tetra- and di(6-azulenyl)cyclobutadiene]cobalt complexes. The redox behavior of these novel (6-azulenyl)benzene derivatives and [t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…In analogy, the reaction of 2-(trimethylsilylethynyl)azulene (8) with one or two equivalents of N-iodosuccinimide led to the formation of the corresponding monoiodo-and diiodoazulenes 10 and 13, respectively, which reacted with Ito et al [26][27][28][29] have recently used a similar methodology with 2-bromo-and 6-bromoazulenes 16 and 18 in order to synthesize 2-ethynyl-and 6-ethynylazulenes 17 and 19, respectively (Scheme 3), and Makosza et al [30] have prepared 6-ethynylazulenes as well as 1,6-di-and 1,3,6-triethynylazulenes by means of Vicarious Nucleophilic Substitution (VNS). Finally, Fujimori [31] also reported some time ago a synthesis of 1-ethynyl-and 2-ethynylazulenes (72 %) as well as 1,2-diethynyl-and 1,3-diethynylazulenes (23-26 %) from the corresponding aldehydes by treatment with lithium trimethylsilyldiazomethane, although without giving experimental details.…”
Section: Synthesis Of Mono- Di-and Triethynylazulenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In analogy, the reaction of 2-(trimethylsilylethynyl)azulene (8) with one or two equivalents of N-iodosuccinimide led to the formation of the corresponding monoiodo-and diiodoazulenes 10 and 13, respectively, which reacted with Ito et al [26][27][28][29] have recently used a similar methodology with 2-bromo-and 6-bromoazulenes 16 and 18 in order to synthesize 2-ethynyl-and 6-ethynylazulenes 17 and 19, respectively (Scheme 3), and Makosza et al [30] have prepared 6-ethynylazulenes as well as 1,6-di-and 1,3,6-triethynylazulenes by means of Vicarious Nucleophilic Substitution (VNS). Finally, Fujimori [31] also reported some time ago a synthesis of 1-ethynyl-and 2-ethynylazulenes (72 %) as well as 1,2-diethynyl-and 1,3-diethynylazulenes (23-26 %) from the corresponding aldehydes by treatment with lithium trimethylsilyldiazomethane, although without giving experimental details.…”
Section: Synthesis Of Mono- Di-and Triethynylazulenesmentioning
confidence: 99%
“…In addition to these novel ethynylazulene derivatives, Ito et al [26][27][28][29] have reported recently on a synthesis of bis- The UV/Vis spectra of the novel ethynyl-bridged oligomers 32, 35 and 36 as well as the monomer 5b are shown in Figure 1. The longest wavelength absorption maximum (λ max ) shifts bathochromically with increasing chain length ( Table 1).…”
Section: Synthesis Of Ethynylene-and Butadiynylene-bridged Oligoazulenesmentioning
confidence: 99%
“…We also recently reported a transition-metal-catalyzed synthesis of arylazulenes. [12] This approach is highly chal-lenging in the case of 1,1Ј-biazulenes, however, due to the instability of the 1-haloazulenes which form a key part of the synthetic pathway. Moreover, preparation of the metal reagents is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Furthermore, we previously reported on the first cyclooligomerization of mono-and diazulen-1-ylethynes by transition metal complexes as an efficient route to novel azulenyl-substituted benzenes and cyclobutadiene complexes. [23] According to the same methodology also some cyclooligomerizations of 2-and 6-ethynylazulenes were investigated later by Ito et al [24,25] Herein, we give a full account of the results of our studies.…”
Section: Introductionmentioning
confidence: 71%